The Economic Burden of Lost Productivity due to Presenteeism Caused by Health Conditions Among Workers in Japan - Yoshimoto, Takahiko (J Occup Environ Med, 2020)
To identify the primary health conditions that cause presenteeism, and to estimate the economic cost of lost productivity due to presenteeism in Japan. METHODS: We conducted an Internet survey among 10,000 Japanese workers. Participants were asked to answer the health condition most affecting their work. Presenteeism was evaluated using the Quantity and Quality methods, and we estimated an annualized cost per capita and nation. RESULTS: The common health conditions most interfering with work were neck pain or stiff shoulders, low back pain, and mental illnesses. The annualized costs of presenteeism per capita for each were $414.05, $407.59, and $469.67, respectively. The estimated national costs for each were all above $27 billion. CONCLUSIONS: Mental illnesses and musculoskeletal symptoms were the leading causes of presenteeism in Japan, and the economic burden of presenteeism was considerably large.